Multi-Stage Magma Evolution in Intra-Plate Volcanoes: Insights From Combined in situ Li and Mg–Fe Chemical and Isotopic Diffusion Profiles in Olivine - Steinmann, Lena K.; Oeser, Martin; Horn, Ingo; Weyer, Stefan (Frontiers in Earth Science, 2020)
Olivines from two locations in the Massif Central volcanic region (France) have been investigated and lithium chemical and isotopic profiles have been determined. The shape and orientation of both the chemical and isotopic profiles indicate that they were dominantly generated by Li diffusion into and within the olivine grains during magmatic evolution and could be modeled in combination with existing Mg and Fe isotope inter-diffusion profiles. Extremely low δ7Li-values down to -30.7 ‰ (relative to IRMM-16) in the crystal core region and elevated values at the crystal rims (δ7Li 8 to 10 ‰), along with increasing concentrations from cores ( 3 to 1 µg/g) towards the rim (12 to 6 µg/g) have been found. While Mg-Fe isotope and chemical profiles have been modeled by a single diffusive event (Oeser et al., 2015), concentration and isotope profiles of the fast-diffusing Li indicate a second diffusive event, which is not detectable by the slower Mg-Fe exchange diffusion couple. Time scales of the first diffusion event were taken from Oeser et al. (2015) based on Mg-Fe isotopic exchange diffusion modeling with well-determined diffusion coefficients which have been interpreted as the residence time of the olivine crystals in a magma chamber. This first event also generated the low δ7Li observed in olivine cores. Comparison of the length of the Mg-Fe and Li profiles could thus be used to determine the less well-known diffusion coefficients of Li in the studied olivine crystals. This latter event might represent a more short-lived degassing process, related to the ascent of the magma prior to eruption. Such a process would only affect Li, which behaves volatilely during degassing, but not the refractory elements Fe and Mg. The findings of this study show that the combined use of isotopic diffusion systems with different diffusion rates, i.e. of spatially resolved δ7Li and Mg-Fe isotope diffusion profiles, is a powerful tool to model even multi-stage evolution processes in a magmatic system. Potentially, Li diffusion, at typically low Li concentration levels in natural olivine, is coupled to that of other slower-diffusing elements, which is not the case at higher concentration levels in laboratory experiments.